USO DE ÓLEO VEGETAL OZONIZADO NA INATIVAÇÃO IN VITRO DE CANDIDA ALBICANS E CANDIDA TROPICALIS - GIMENEZ, Vanessa Barbosa; GIMENEZ, Andressa Barbosa; LIMA, Alice Ferreira de; MENDES, Elena Carla Batista; GONÇALVES, Jussara Britto Batista; KOZUSNY-ANDREANI, Dora Inés (UNIFUNEC CIENTÍFICA MULTIDISCIPLINAR, 2025)
Objetivo: Avaliar a eficácia de óleos vegetais ozonizados na inativação in vitro de Candida albicans ATCC 25923 e Candida tropicalis ATCC 4563. Métodos: Estudo experimental quali-quantitativo, de natureza descritiva-exploratória, onde foi avaliada a eficácia fungicida dos óleos de coco, dendê, girassol, oliva e de pequi, nas formas in natura e ozonizados em concentrações que variaram de 0,32% a 100%. Foi determinada a concentração inibitória mínima pelo método de microdiluição em placa, posteriormente avaliada a concentração fungicida mínima e a cinética fungicida dos óleos. Resultados: Os resultados evidenciaram atividade antifúngica para os óleos de girassol, coco, dendê, pequi e oliva, in natura e ozonizados na inativação de Candida tropicalis e Candida albicans. Em relação à capacidade de redução das unidades formadoras de colônias em função do tempo, verificou-se que os óleos de oliva e de pequi, ozonizados e in natura foram mais eficazes. Considerações Finais: Os resultados apontam a possibilidade de utilização na terapêutica de Candida albicans e tropicalis. USE OF OZONIZED VEGETABLE OILS IN THE IN VITRO INACTIVATION OF CANDIDA ALBICANS AND CANDIDA TROPICALIS ABSTRACT Objective: To evaluate the effectiveness of ozonized vegetable oils in the in vitro inactivation of Candida albicans ATCC 25923 and Candida tropicalis ATCC 4563. Methods: This was a descriptive-exploratory experimental study with a qualitative and quantitative approach. The fungicidal activity of coconut, palm, sunflower, olive, and pequi oils, both in their natural form and ozonized, was evaluated at concentrations ranging from 0.32% to 100%. The minimum inhibitory concentration (MIC) was determined using the microdilution method in plates, followed by determination of the minimum fungicidal concentration (MFC) and fungicidal kinetics of the oils. Results: The findings demonstrated antifungal activity of sunflower, coconut, palm, pequi, and olive oils, both natural and ozonized, in the inactivation of Candida tropicalis and Candida albicans. Regarding colony-forming unit (CFU) reduction over time, ozonized and natural olive and pequi oils showed greater efficacy. Conclusions: The results indicate the potential therapeutic use of ozonized vegetable oils against Candida albicans and Candida tropicalis. Keywords: Candida; antifungals; vegetable oil; ozone.